Principles of Economics - Frank Robert H (McGraw Hill/Irwin, 2004)
In recent years, innovative texts in mathematics, science, foreign languages, and other fields have achieved dramatic pedagogical gains by abandoning the traditional encyclopedic approach in favor of attempting to teach a short list of core principles in depth. Two well-respected writers and researchers, Bob Frank and Ben Bernanke, have shown that the less-is-more approach affords similar gains in introductory economics. Although recent editions of a few other texts have paid lip service to this new approach, Frank/Bernanke is by far the best thought out and best executed principles text in this mold. Avoiding excessive reliance on formal mathematical derivations, it presents concepts intuitively through examples drawn from familiar contexts. The authors introduce a well-articulated short list of core principles and reinforcing them by illustrating and applying each in numerous contexts. Students are periodically asked to apply these principles to answer related questions, exercises, and problems.